A high prevalence of arterial hypertension in patients with mitochondrial diseases. Issue 3 (15th December 2019) - Chong‐Nguyen, Caroline; Stalens, Caroline; Goursot, Yves; Bougouin, Wulfran; Stojkovic, Tanya; Béhin, Anthony; Mochel, Fanny; Berber, Nawal; Eymard, Bruno; Duboc, Denis; Laforêt, Pascal; Wahbi, Karim
Abstract: The prevalence of arterial hypertension in mitochondrial diseases remains unknown. Between January 2000 and May 2014, we retrospectively included patients with genetically proven mitochondrial diseases. We recorded clinical, genetic and cardiac exploration data, including the measure of arterial pressure. Among the 260 patients included in the study (mean age = 44 ± 15 years, women = 158), 108 (41.5%) presented with arterial hypertension. The prevalence of hypertension by sex and age was higher than that observed in the general population for all groups. The prevalence of hypertension was significantly higher in patients with MELAS (mitochondrial encephalopathy, lactic acidosis, and stroke‐like episodes) mutations (66%) and MERRF (myoclonus, epilepsy, ataxia with ragged ref fibres) mutations (61%). In patients with MELAS mutation, the presence of hypertension was significantly associated with age and mutation rate in the blood (odds ratio = 1.12; P = .02) in multivariate analysis. The prevalence of hypertension was more important in patients having a mitochondrial disease. The increased risk was more important in patient with MELAS or MERRF and depended on the rate of heteroplasmy.